THE INFLUENCE OF WORD STRESS ON EFL LEARNERS' TOT STATE - Mailawati; Sutrisno, Adi (Leksema: Jurnal Bahasa dan Sastra, 2023)
Tip of the Tongue (ToT) is a condition that hinders the production of fluency in speech. This study aims to identify stress patterns and factors that influence the emergence of ToT states. This research used a quantitative approach with the basis of ToT analysis theory from Brown and McNeill. For collecting data, it used an experimental design with EFL students in Kampung Inggris Pare as the objects by involving total 15 participants aged from 18th to 21st years old or late teens. The results show that the language features appearing from the experiment including words (65%), first syllables (24%), last syllables (3%), and letters (6%). The first syllable shows 21% occurrences more than that of the last syllable. There is no identification of stress in the completion of ToT in terms of the appearance of the dominating first syllable. It means that stress does not affect the completion of the ToT, but the frequency of syllables. The other factors that affect ToT in EFL include the mental processes of EFL learners, the sound imitations towards direct communication, and the teacher's role in teaching pronunciation.